"Fully alive: awakening health, humor, compassion and truth" - "Lebrun, Louise" (Bhopal, 2008)
Awaken body, mind and soul by putting responsibility and power back to where they belong. Identify the habits of thought that prevent us from taking action. Cutting-edge science and principles from quantum biology show us how we are part of the problem and how we can become a dynamic force in the solution.
Keywords: Personal development